2022
DOI: 10.1086/721478
|View full text |Cite
|
Sign up to set email alerts
|

Within-Generation and Transgenerational Plasticity of a Temperate Salmonid in Response to Thermal Acclimation and Acute Temperature Stress

Abstract: Brook trout (Salvelinus fontinalis) exhibit within-generation and transgenerational plasticity for thermal performance, although neither response appears sufficient to cope with long-term climate change effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
1
5
1
Order By: Relevance
“…We also found that Fulton's index of second‐year fish in laboratory environment was influenced by the temperature treatment, with fish from cold‐acclimated parents having a lower index than those from warm‐origin adults. This result contrasts with those presented in Penney et al (2022), where Brook charr juveniles from cold‐acclimated parents had better body condition than those from warm‐acclimated parents. In this study, however, differences in temperature between cold and warm treatment were more important (10°C or 21°C, for cold and warm respectively), and were maintained for a longer period in separate treatments (from May until fall reproduction) than in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We also found that Fulton's index of second‐year fish in laboratory environment was influenced by the temperature treatment, with fish from cold‐acclimated parents having a lower index than those from warm‐origin adults. This result contrasts with those presented in Penney et al (2022), where Brook charr juveniles from cold‐acclimated parents had better body condition than those from warm‐acclimated parents. In this study, however, differences in temperature between cold and warm treatment were more important (10°C or 21°C, for cold and warm respectively), and were maintained for a longer period in separate treatments (from May until fall reproduction) than in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, sire identity explained a significant proportion of the variation in survival at that same period. Our findings are in line with those of Penney et al (2022) that revealed a greater contribution of sires, relative to dams, to transgenerational effects in Brook charr families produced from parents acclimated to cold and warm temperatures and kept in controlled conditions. Again, however, we recognize that low survival and a small number of families in the cold treatment may have hampered our results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations